PENGARUH BRAND AMBASSADOR DAN TESTIMONI TERHADAP KEPUTUSAN PEMBELIAN ATAS PRODUK ZENIA CLINIC DI KECAMATAN KINALI (Studi: Zenia Clinic Kinali) - Yulia Eka Putri; Amsah Hendri Doni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research aims to identify the extent of the impact of brand ambassadors and evidence on purchasing decisions on Zenia Clinic products in Kinali District. The method used in this research is a quantitative method. This research was conducted with 95 respondents. On the other hand, the method of collecting information was attempted by distributing questionnaire forms which were then processed using SPSS 24. The analysis tools used in this research are instrument trials (validity and reliability trials), classical assumption trials (normality trials, multicollinearity trials and heteroscedasticity trials), multiple linear regression trials, coefficient of certainty trials (R2) and assumption trials (partial significance trials (T-test) and simultaneous significance trials (F-test)). The results of this research prove that the T-test of brand ambassador (X1) on purchasing decisions (Y) is 0.001≤0.05 and the t-count is 9.965≥ t-table 1.985. This means that H1 is obtained where there is an effect of brand ambassador (X1) on purchasing decisions (Y) in a significant way. The T-test of evidence (X2) on purchasing decisions (Y) is 0.001≤0.05 and the t-count is 9.631≥ t-table 1.985. This means that H2 is obtained where there is an effect of evidence (X2) on purchasing decisions (Y) in a significant way. The results of the F-test prove that the significant number of effects of brand ambassadors (X1) and proof (X2) on purchasing decisions (Y) is 0.001 ≤ 0.05 and the f count is 66.169 ≥ ftable 3.09. This means that there is a simultaneous effect between brand ambassadors (X1) and proof (X2) on purchasing decisions. (Y).